Domain growth in LiNbO3 with surface layer modified by soft proton exchange. Issue 1 (19th May 2022) - Savelyev, E. D.; Akhmatkhanov, A. R.; Greshnyakov, E. D.; Abramov, A. S.; Tronche, H.; Doutre, F.; Lunghi, T.; Baldi, P.; Neradovskiy, M. M.; Shur, V. Ya.
Abstract: We present the study of domain growth in congruent LiNbO3 crystals with planar soft proton exchanged waveguides (CLN SPE). The spatial distribution of H ions was measured by confocal Raman microscopy. The growth of elongated irregular shape domains followed by slow domain widening was obtained. Domain approaching led to a change in the growth directions. Domain widening represented formation of submicron domains with depth of tens microns in front of the domain walls. Low threshold field is attributed to the surface composition gradient. The suppression of hexagonal domain growth is related to existence of the surface dielectric layer.